Pengaruh Motivasi Kerja, Budaya Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan pada CV Batam Pangan Mandiri - Alya Natasyah; Sumardin Sumardin; Muhammad Sidik (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Human resources play a strategic role in determining organizational success and sustainability. Employee performance is one of the most important indicators of organizational effectiveness because it reflects the achievement of organizational goals through employees’ work outcomes. However, employee performance may be influenced by several factors, including work motivation, work culture, and work environment. This study aimed to analyze the effect of work motivation, work culture, and work environment on employee performance at CV Batam Pangan Mandiri, both partially and simultaneously. This research employed a quantitative approach using multiple linear regression analysis. The study involved all 45 employees of CV Batam Pangan Mandiri as respondents through a saturated sampling technique. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using SPSS version 19.0. The findings revealed that work environment was the most dominant factor influencing employee performance, contributing 33.60%, followed by work culture at 30.50% and work motivation at 11.50%. Simultaneously, work motivation, work culture, and work environment had a significant effect on employee performance, with an F-value of 18.436 and a coefficient of determination of 55.10%. These results indicate that improving employee performance requires an integrated approach involving strong work motivation, a positive work culture, and a supportive work environment.